Factors Affecting Customer Satisfaction on Skincare Brand: Somethinc - Putri Vika Noerindah; Innocentius Bernarto (Institute of Computer Science (IOCS), 2022)
The popularity of beauty products has risen quite rapidly in this era of globalization and Indonesia has seen growth in this industry despite the pandemic. One of the popular brands is SomeThinc, a company that specialized in beauty products and one of the biggest beauty product brands that utilize e-commerce as selling platform. This research attempted to clarify whether Brand Awareness, Price Fairness, and Product Quality have effects towards Customer Satisfaction on this beauty product brand. By using these 3 vairables and also SEM-PLS method to analyse 401 respondent data and it can be concluded that these three variables have positive effect towards Customer Satisfaction on SomeThinc beauty products..